SURFACE SOLITARY WAVES IN A DOUBLE DIFFUSIVE SYSTEM - Kraenkel, Roberto André [UNESP]; Pereira, J. G.; Manna, M. A. (Royal Swedish Acad Sciences, 1992)
We show that a surface solitary wave governed by the Korteweg-de Vries equation can develop in a fluid acted upon by fluxes of heat and of a second diffusive element. This solitary wave appears as a manifestation of a hydrodynamical instability which sets in only when a certain relation involving the parameters of the system is satisfied.